Terretonin as a New Protective Agent against Sepsis-Induced Acute Lung Injury: Impact on SIRT1/Nrf2/NF-κBp65/NLRP3 Signaling - Gamal A. Mohamed (MDPI AG, 2021)
Endophytic fungi are proving to be an excellent source of chemical entities with unique structures and varied bioactivities. Terretonin (TE) and its structurally related derivatives are a class of meroterpenoids, possessing the same unique tetracyclic core skeleton, which have been reported from the Aspergillus genus. This study was carried out to assess the potential protective effects of TE separated from the endophytic fungus A. terreus against LPS (lipopolysaccharide)-induced ALI (acute lung injury) in mice. The results revealed that TE alleviated pulmonary edema as it lowered both the W/D lung ratio and protein content. The inflammatory response represented by inflammatory cell infiltration into the lung tissues was greatly repressed by TE. That was supported by the improved histopathological results and also by the reduced level of myeloperoxidase in the lung. TE showed a potent antioxidant activity as it attenuated lipid peroxidative markers (malondialdehyde, 4-hydroxynonenal, and protein carbonyl) and enhanced endogenous antioxidants (reduced glutathione, superoxide dismutase, and catalase) in lung tissues. Similarly, TE increased the mRNA expression of SIRT1, Nrf2, and its genes (HO-1, NQO1, and GCLm). On the other hand, TE restrained the activation of NF-κB (nuclear factor-κB) in the lung. Consequently, TE depressed the pro-inflammatory cytokines: nitric oxide (NOx), TNF-α (tumor necrosis factor-α), and interleukins (IL-6 and -1β). Additionally, TE inhibited NLRP3 signaling and interrupted apoptosis by decreasing the levels of proapoptotic markers (Bax and caspase-3) and increasing the level of an anti-apoptotic marker (Bcl-2). In conclusion, TE had a remarkable protective potential on LPS-induced lung damage via antioxidant and anti-inflammatory mechanisms. This finding encourages further investigations on this promising candidate.